Land Use Change and Mountain Biodiversity - Spehn, Eva (CRC Press, 2009)
Part of the worldwide biodiversity program DIVERSITAS, the Global Mountain Biodiversity Assessment (GMBA) assesses the biological richness of high-elevation biota. GMBA's focus includes the uppermost forest regions or their substitute rangeland vegetation, the treeline ecotone, and the alpine and nival belts. Providing more than description, the GMBA explains the causes of biological richness and how diversity changes over time. Because biodiversity changes often result from human land use, part of the GMBA agenda is the assessment of land use impacts. These assessments are critical in low-latitude regions, where land use pressure on upland biota is the greatest.